Ensino de leitura de frases com compreensão a crianças de segunda série do ensino fundamental - ALBUQUERQUE, Eliana dos Santos (2007)
The aim of this study was to verify the efficiency of teaching reading comprehension using sentences containing three types of words (a pronoun, a noun, and an adjective), based on the equivalence paradigm, and thereby extending verbal units utilized in a previous investigation. The sample was composed of five second grade children with reading difficulties from public schools in Belem, Para. There were five experimental phases including, pretests, teaching, intermediate and post-tests. The AB and AC relations were taught by use of syllables, words and sentences according to a specific stimulus modality: verbalized by the experimenter, pictorial and printed. The following equivalence relations were assessed, verbal naming and generalized word reading (Generalization I); two-word sentences (Generalization II and III), and three-word sentences (Generalization IV). The criterion for success was 100% correct responses in each trial block, with differential consequences. After the last phase the number of correct and incorrect responses without differential consequences was evaluated. The students responded consistently to the teaching criterion method. On Generalization Test I, three participants responded readily to new words. On Generalization Tests II and III, all of the participants read each new twoword sentence. On the Generalization Test IV, only two participants read all of the newly presented three-word sentences. After 30 days, of the four participants that remained in the experiment, two maintained the same level of generalized two-word sentences, whereas only one read consistently the generalized three-word sentences. In comparison with a previous study that used only two-word sentences, these results demonstrated the positive effect of the procedure. In theoretical, methodological and social terms, the findings may have educational relevance and make significant contributions to the teaching of reading comprehension. Future research using the facilitating procedures implicit in verbal unit reading, as based on the stimulus equivalence paradigm, appears especially promising.